Perlindungan Hukum Nasabah atas Penggunaan E-Banking - Pakhry Nugroho Kadari; Saharuddin Saharuddin; Muh. Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2023)
This research is a normative legal research. This research will examine the principles, legal concepts and laws and regulations related to the legal protection of bank customers for the use of Internet-Banking. In order to obtain research materials, the research will be carried out by means of a literature study that examines legal materials. Legal materials as research materials are taken from library materials in the form of primary legal materials, secondary legal materials, and tertiary legal materials. Legal materials and non-legal materials obtained in this study will be analyzed prescriptively with the deductive method. The results of this study indicate that forms of legal protection for users of internet banking services can be seen from several provisions, namely Law No. 8 of 1999 concerning consumer protection. However, it is very regrettable that some of these provisions have not been good enough in providing legal protection for consumers who use internet banking because law enforcement has not been implemented. Thus, the legal protection that is expected to be enjoyed by the community does not and/or has not occurred. And law no. 8 of 1999 concerning consumer protection, some of its rules still have many weaknesses and shortcomings, namely the lack of relevance of the rules to current legal issues, especially those related to technology.